Gapless reference genome assembly of Didymella glomerata, a new fungal pathogen of maize causing Didymella leaf blight - Ma, Wendi; Yang, Jun; Ding, Junqiang; Zhao, Wensheng; Peng, You-Liang; Bhadauria, Vijai (Frontiers in Plant Science, 2022)
Didymella leaf blight (DLB) caused by Didymella glomerata is a new fungal disease of maize (Zea mays), first detected in 2021 in Panjin, Liaoning province of China. Here we report the reference genome assembly of D. glomerata to unravel how the fungal pathogen controls its virulence on maize at the molecular level. A maize-infecting strain Pj-2 of the pathogen was sequenced on the Illumina NovaSeq 6000 and PacBio Sequel II platforms at a 575-fold genomic coverage. The 33.17 Mb gapless genome assembly comprises 32 scaffolds with L/N50 of 11/1.36 Mb, four of which represent full-length chromosomes. The Pj-2 genome is predicted to contain 10,334 protein-coding genes, of which 211, 12 and 134 encode effector candidates, secondary metabolite backbone-forming enzymes and CAZymes, respectively. Some of these genes are potentially implicated in niche adaptation and expansion, such as colonizing new hosts like maize. Phylogenomic analysis of eight strains of six Didymella spp., including three sequenced strains of D. glomerata, reveals that the maize (Pj-2)- and Chrysanthemum (CBS 528.66)-infecting strains of D. glomerata are genetically similar (sharing 92.37% genome with 98.89% identity), whereas Pj-2 shows truncated collinearity with extensive chromosomal rearrangements with the Malus-infecting strain M27-16 of D. glomerata (sharing only 55.01% genome with 88.20% identity). Pj-2 and CBS 528.66 carry four major reciprocal translocations in their genomes, which may enable them to colonize the different hosts. Furthermore, germplasm screening against Pj-2 led to the identification of three sources of DLB resistance in maize, including a tropical inbred line CML 496. DLB resistance in the line is attributed to the accumulation of ROS H2O2 in the apoplastic space of the infected cells, which likely restricts fungal growth and proliferation.